SEAGRASS ECOSYSTEM IN THE COASTAL AREA OF SOUTHERN KEI BESAR DISTRICT, SOUTHEAST MALUKU REGENCY, PROVINCE OF MALUKU, INDONESIA - Marsya Jaqualine Rugebregt (Widyariset, 2015)
The aims of this research were to determine the seagrass bed coverage and its ecosystem condition. The research result obtained ten seagrass species, those are Cymodocea serullata, Cymodecea rotundata, Syringodium isotefilium, Halophila ovalis, Halophila minor, Enhalus acroides, Halodule pinifolia, Halodule uninervis, Thalassia hempirichii, and Thalossodenron ciliatum. The biggest percentage of seagrass coverage was found in Tamangil Nuhuten (50,75 %), followed by Tamangil Nuhuyanat (62,61%), Soindrat (51,53%), Ngafan (58,70%), dan Tutrean (57,15%).Water quality of this area was good for the life of seagrass.